Cellular internalization in the absence of invasin expression is promoted by the Yersinia pseudotuberculosis yadA product. - Yang, Y (1993)
The Yersinia pseudotuberculosis invasin protein is able to promote bacterial penetration into mammalian cells. Insertion mutations that eliminate production of this protein show residual internalization that is dependent on the presence of the Yersinia virulence plasmid. An enrichment procedure was used to isolate molecular clones containing regions of the virulence plasmid that confer this low-level uptake on Y. pseudotuberculosis inv mutants. All of the Y. pseudotuberculosis strains isolated from this procedure harbored plasmids containing a region encompassing the yadA gene, which encodes a previously identified adhesin associated with attachment to extracellular matrix proteins. All of the mutations isolated that affected internalization of one of the strains that survived the enrichment disrupted the yadA open reading frame. Furthermore, a strain that contained yadA sequences and no other region of the virulence plasmid was able to promote internalization of a Y. pseudotuberculosis inv mutant. Consistent with these results, an intact virulence plasmid containing an insertion mutation in yadA was as defective as a plasmid-cured strain at promoting uptake of Y. pseudotuberculosis inv mutants. These results indicate that the product of the yadA gene is responsible for the plasmid-dependent entry observed in Y. pseudotuberculosis inv mutants.